1997
DOI: 10.1136/oem.54.7.524
|View full text |Cite
|
Sign up to set email alerts
|

In vitro percutaneous penetration of methyl-parathion from a commercial formulation through the human skin.

Abstract: Objective-To compare in vitro percutaneous absorption ofmethyl-parathion dissolved in an acetone vehicle and in the form of a commercial formulation. Methods-Penetration through the human skin was measured in Franz diffusion cells with full thickness skin from a human cadaver as the membrane. The two tailed non-parametric Mann-Whitney U test was used to compare the cumulative diffusion of methyl-parathion in the receptor fluid of the cells at various time intervals.Results-In vitro skin penetration of methyl-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 7 publications
0
10
1
Order By: Relevance
“…Results show no percutaneous penetration of PAHs contained in the two types of carbon (their concentration in the receptor¯uid was under detection limits) with a passage through the skin of the compounds when they were in dierent vehicles (acetone solution with arti®cial sweat). Even the presence of solvents in commercial formulations can change penetration rates of chemicals [8].…”
Section: Discussionmentioning
confidence: 99%
“…Results show no percutaneous penetration of PAHs contained in the two types of carbon (their concentration in the receptor¯uid was under detection limits) with a passage through the skin of the compounds when they were in dierent vehicles (acetone solution with arti®cial sweat). Even the presence of solvents in commercial formulations can change penetration rates of chemicals [8].…”
Section: Discussionmentioning
confidence: 99%
“…The mean lag time for methylparathion has previously been estimated to vary between 3 and 7 hours depending on formulation 6. With lag times sometimes considerably longer than a normal working day, it becomes increasingly important to study to what extent absorption (the amount of pesticide measurable in the receptor phase) will increase after exposure has stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Although the animals were housed individu-ally, the possibility that some oral absorption might have occurred through grooming cannot be discounted. Sartorelli et al (1997) demonstrated the in vitro percutaneous penetration of methyl parathion through the human skin. Similar results were obtained in experimental animals for dermal application of other organophosphorus insecticides such as leptophos (Omethyl O-4-bromo-2,5-dichlorophenyl phenylphosphonothioate;Abou-Donia,1979) and EPN (O-ethyl O-4-nitrophenyl phenylphosphonothioate;Abou-Donia et al,1983).…”
Section: Discussionmentioning
confidence: 99%